Micropropagation protocol for the wild Brazilian greenberry (Rubus erythroclados) - Bueno, Paulo Mauricio Centenaro; Biasi, Luiz Antonio; Tofanelli, Mauro Brasil Dias (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This study presents the first micropropagation protocol for greenberry (Rubus erythroclados), a wild Brazilian species with edible green fruits. In the in vitro multiplication stage, three concentrations of benzyladenine (BA) were tested (0, 5 and 10 μM), combined with three concentrations of indolebutyric acid (IBA) (0, 3 and 6 μM) in two subsequent subcultures. In the rooting stage, in and ex vitro rooting were compared after pulse treatment of the microcutting for 10 seconds in IBA (0, 2.46, 4.92 and 7.38 mM). For the in vitro trial, the microcuttings were maintained in glass bottles with an MS medium under controlled conditions inside a growth room. For the ex vitro trial, the microcuttings were planted in styrofoam containers with vermiculite and maintained inside a greenhouse with an intermittent mist system. R. erythroclados multiplication was obtained with the addition of BA to the culture medium, while IBA reduced the shoot proliferation and increased mortality. The ex vitro rooting showed the best results, reaching 95.8% for rooted and acclimatizated plants without IBA. An efficient and simple protocol can be used for R. erythroclados micropropagation with 5 μM BA for in vitro shoot proliferation and ex vitro rooting of microcuttings with intermittent misting.